The concept of industrial enterprise development management - Igor Filipishyn (Cхід)
A distinctive feature of the concept of enterprise development management is to ensure comprehensive economic analysis for a continuous goal-setting, and their relationship with the combined management approach, that includes the management by objectives and management by deviations.